Catalytic production of tetrahydropyran (THP): a biomass-derived, economically competitive solvent with demonstrated use in plastic dissolution. Issue 23 (11th November 2022) - Dastidar, Raka G.; Kim, Min Soo; Zhou, Panzheng; Luo, Zaneta; Shi, Changxia; Barnett, Kevin J.; McClelland, Daniel J.; Chen, Eugene Y.-X.; Van Lehn, Reid C.; Huber, George W.
Abstract : Tetrahydropyran (THP) is a five-carbon heterocyclic ether that is non-carcinogenic, non-peroxide forming, biodegradable, and economically competitive with tetrahydrofuran (THF) as a solvent. Abstract : Tetrahydropyran (THP) is a five-carbon heterocyclic ether that is non-carcinogenic, non-peroxide forming, biodegradable, and economically competitive with tetrahydrofuran (THF) as a solvent. In this work, THP has been synthesized from renewable biomass at >99.8% selectivity and 98% yield via hydrogenation of furfural-derived 3, 4-dihydropyran (DHP) over Ni/SiO2 in a continuous flow reactor at 150–200 °C. The apparent activation energy of THP formation is 31 kJ mol −1, and the reaction orders with respect to the partial pressures of H2, DHP, and THP are: 2, 1, and −0.3. The kinetic data has been fitted to a Hougen–Watson model where the rate limiting step is the hydrogenation of adsorbed DHP. Ni/SiO2 is shown to have a low deactivation rate constant of 0.012 h −1 over 100 h time on stream and can be regenerated in situ . As a performance advantage, THP is shown to be resistant to ring opening polymerization under strongly acidic conditions that THF is not, revealing it to be a superior solvent. The minimum selling price of THP is competitive with the market price of THF ($900–1400 per ton) at a DHP feedstock cost of $1000 per ton. Conductor-like Screening Model for Real Solvents (COSMO-RS) and molecular dynamics (MD) simulations with 1008 solvents and 8 common plastics have demonstrated that THP can serve as an alternative solvent to THF, 2-methyltetrahydrofuran (MeTHF), and cyclopentyl methyl ether (CPME) for plastic dissolution, especially low-density polyethylene (LDPE), polypropylene (PP), polystyrene (PS) and polyvinyl chloride (PVC). This work establishes THP as a green solvent with excellent thermal, chemical and peroxidative stability that can be used for numerous applications, including waste plastic recycling.